The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/jvi.01276-15
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glycosaminoglycans Affects PrPScMetabolism but Does Not Block PrPScUptake

Abstract: Mammalian prions are unconventional infectious agents composed primarily of the misfolded aggregated host prion protein PrP, termed PrP Sc . Prions propagate by the recruitment and conformational conversion of cellular prion protein into abnormal prion aggregates on the cell surface or along the endocytic pathway. Cellular glycosaminoglycans have been implicated as the first attachment sites for prions and cofactors for cellular prion replication. Glycosaminoglycan mimetics and obstruction of glycosaminoglycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
(105 reference statements)
1
18
0
Order By: Relevance
“…By FRET, it was observed that when cells are D r a f t treated with heparinase, a significant decrease of propagation occurs. A similar effect of GAGmediated aggregates propagation was reported for the prion protein (Wolf et al 2015).…”
Section: Biological Relevance Of Gag-mediated Amyloid Assemblysupporting
confidence: 78%
“…By FRET, it was observed that when cells are D r a f t treated with heparinase, a significant decrease of propagation occurs. A similar effect of GAGmediated aggregates propagation was reported for the prion protein (Wolf et al 2015).…”
Section: Biological Relevance Of Gag-mediated Amyloid Assemblysupporting
confidence: 78%
“…PrP c and PrP Sc interacting receptors, like glycosaminoglycans (GAGs), laminin receptor precursor (LRP/LR), and LRP1, have a prominent role in the conversion process. It has been demonstrated that cultured cells harboring reduced amounts or modified GAGs, such as heparin sulfate, are resistant to primary prion infection [ 60 , 61 ]. Interfering with lipid raft formation by drugs, such as lovastatin, filipin, and amphotericin B, was capable of reducing PrP Sc levels in neuroblastoma cell lines persistently infected with scrapie prion strains, thus emphasizing the role of lipid rafts in PrP Sc conversion [ 47 , 55 , 62 ].…”
Section: Prp C Trafficking and Its Role In Prp mentioning
confidence: 99%
“…4a). Murine fibroblast cell line L929 39 and CAD5 cells 40 , two cell lines highly permissive to TSE strain 22L, were exposed to VSV-G positive EV (Fig. 4b) and subsequently cultured in the absence of EV for more than 8 passages before testing for the formation of PrP Sc (Fig.…”
Section: Vsv-g-pseudotyped Ev Efficiently Transmit Scrapie Prions To mentioning
confidence: 99%